The wheat TaIQD3D-6 gene encodes a microtubule-associated protein and regulates cell morphogenesis in Arabidopsis. (November 2022) - Liu, Haofeng; Cao, Yongxin; Zhang, Wenjing; Liu, Zhu; Li, Yan; Chen, Yu; Zhang, Hongchang; Yu, Fei; Liu, Xiayan
Abstract: A plethora of microtubule-associated proteins (MAPs) modulate the dynamics of microtubules (MTs) to ensure the proper elaboration of developmental programs in plants. Among the plant-specific MAPs are the IQ67 domain (IQD) family proteins. Despite the great progress in elucidating IQD protein functions, the majority of IQD proteins, especially IQDs in crop species, remain to be functionally explored. In this study, we identified 78 putative IQD family genes in the genome of hexaploid wheat ( Triticum aestivum ). Phylogenetic analysis of wheat and Arabidopsis IQDs supports the previous notion that the expansion of the IQD family coincides with plant terrestrialization. Further characterization of one TaIQD, TaIQD3D-6, revealed that TaIQD3D-6 directly binds to MTs and free tubulins in vitro and is associated with cortical MTs in interphase cells in vivo. Overexpressing TaIQD3D-6 in Arabidopsis leads to a spectrum of phenotypes that are indicative of perturbed MT homeostasis, including spiral growth, hypersensitivity to MT-destabilizing drugs, defects in cell morphogenesis, and altered organization of cMT arrays. Finally, we determined that TaIQD3D-6-GFP localizes to the expanding cell plate during cytokinesis and the overexpression of TaIQD3D-6 interferes with asymmetric cell division in the stomatal lineage in Arabidopsis. In summary, our findings establish that TaIQD3D-6 is a MAP that regulates plant cell and organ morphogenesis and provide new insights into the functions of crop IQD proteins. Highlights: IQD gene family in hexaploid wheat ( Triticum aestivum ) contains at least 78 members. One wheat IQD protein, TaIQD3D-6, is associated with microtubules in vitro and in vivo. The overexpression of TaIQD3D-6 in Arabidopsis perturbs MT homeostasis and leads to left-handed helical growth. The overexpression of TaIQD3D-6 interferes with asymmetric cell divisions in the stomatal lineage in Arabidopsis.